The Impact of Market Service and Recreational Levies on Regional Revenue: Empirical Evidence from Central Java, Indonesia - Tardin, Tardin (International Journal of Marketing & Human Resource Research, 2025)
This study aims to determine how market service levies and levies on recreation and sports venues affect local original income in five districts within the Central Java Province between 2017 and 2022. This study employs a quantitative methodology and uses secondary data, specifically the budget realization report from the Central Java Province. Six cities and 29 districts made up the study's population. In order to get 30 pieces of research data, the study sample collected data from 5 districts in the Central Java Province between 2017 and 2022. The analytical techniques employed include multiple linear regression analysis, traditional assumption testing, and descriptive statistical analysis. Using the Eviews Version 12 Software test tool, hypothesis testing employed the t test and coefficient of determination (R2). According to the study's findings, Original Regional Income in five Central Java Province districts increased due to Market Service Retributions between 2017 and 2022. As a result, the PAD in that region rises in proportion to the Market Service Levy and vice versa. The Central Java Province's five districts' original regional income for 2017–2022 is unaffected by the recreation and sports facilities levy. This is due to the fact that the expenses incurred in maintaining sports and recreation facilities exceed the revenue generated by these levies. Restrictions brought on by the Covid-19 epidemic also contributed to this drop.